Inovasi Pembelajaran Pendidikan Agama Islam Serta Peluang dan Tantangannya Dalam Menghadapi Era Society - Sinulingga, Neng Nurcahyati; Firmansyah, Firmansyah; Dalimunthe, Amsal Qori; Ginting, Matius Ocon (AN NUR: Jurnal Studi Islam, 2023)
This study aims to describe the development of PAI learning innovation and its opportunities and challenges in facing the era of society. More specifically, the problem formulation studied in this research is about PAI learning innovation in the era of society, the media form of PAI learning innovation in the era of society, and the opportunities and challenges in implementing PAI innovation in the era of society. This research is qualitative research with a literature review, whose data can be analyzed relevantly and interpretatively. The findings of this study show that the era of society greatly impacts PAI learning innovation. The e-learning application with various learning activities that make it easy for teachers and students to access learning online is a type of PAI learning innovation media that is developing in today's society. Besides e-learning, there are other supporting learning media available such as Skype and Zoom, Google Meet, Discord, and Edmodo. PAI learning innovations today present opportunities and challenges, as for the opportunities: (1) train critical thinking and problem-solving skills, (2) train communication skills, (3) train creativity and innovation skills, in addition to opportunities there are also challenges in implementing PAI innovation media in the era of society, including (1) declining moral values, (2) digital literacy, (3) method innovation, (4) qualified human resources.